2002
DOI: 10.1093/oxfordjournals.schbul.a006971
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Prediction Model of Schizophrenia

Abstract: Univariate prediction models of schizophrenia may be adequate for hypothesis testing but are narrowly focused and limited in predictive efficacy. Therefore, we used a multivariate design to maximize the prediction of schizophrenia from premorbid measures and to evaluate the relative importance of various predictors. Two hundred twelve Danish subjects with at least one parent diagnosed in the schizophrenia spectrum (high risk) and 99 matched subjects with no such parent (low risk) were assessed on 25 premorbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 141 publications
4
59
1
2
Order By: Relevance
“…Apart from findings on generalized batteries of tests (eg, Wechsler Intelligence Scale for Children [WISC], 36 Rivermead Behavioral Memory Test 37 ), 29,[38][39][40] relatively more specific domains of vulnerability include visuo-motor development, 41,42 perceptual problems, conceptual sorting, language processing, and possibly mental tracking, sustained attention, short-term memory, working memory, and verbal recognition and recall. 38,[43][44][45][46][47][48] These deficits are moderate, 49 and in cross-sectional studies they have been reported to be greater in relatives with a higher genetic loading.…”
Section: Overview Of Approaches and Rationale For Limits Of Current Rmentioning
confidence: 99%
“…Apart from findings on generalized batteries of tests (eg, Wechsler Intelligence Scale for Children [WISC], 36 Rivermead Behavioral Memory Test 37 ), 29,[38][39][40] relatively more specific domains of vulnerability include visuo-motor development, 41,42 perceptual problems, conceptual sorting, language processing, and possibly mental tracking, sustained attention, short-term memory, working memory, and verbal recognition and recall. 38,[43][44][45][46][47][48] These deficits are moderate, 49 and in cross-sectional studies they have been reported to be greater in relatives with a higher genetic loading.…”
Section: Overview Of Approaches and Rationale For Limits Of Current Rmentioning
confidence: 99%
“…Parenting influences endophenotypes that associate with a wide range of psychopathologies (Rapee, 1997;Carter et al, 2002). The challenge is that of establishing a direct relationship between parental care and the development of the neural systems that mediate the relevant cognitive and emotional endophenotypes, as well as identifying candidate mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been made to optimize the diagnostic process reflected in the evolution of diagnostic criteria from Bleuler's descriptive psychopathology to current elaborated diagnostic concepts of DSM-IV (American Psychiatric Association, 1994) and ICD-10 (World Health Organization, 1993). It has been suggested repeatedly that the inclusion of laboratory tests might improve diagnostic homogeneity of schizophrenia (Sponheim et al, 2001;Carter et al, 2002). However, reliable and objective biomarkers are missing and clinicians still depend on formal diagnostic criteria and their clinical impression, consequently running the risk to bias objective criteria towards subjective experience.…”
Section: Introductionmentioning
confidence: 99%